Sustainable Economic Growth: A Challenge to Embrace for Bangladesh (Global Journal of Human-Social Science, 2019)
The economy of Bangladesh is moving from a predominantly agricultural economy to a service sector dominated industry-based economy. In recent times, the word sustainable growth becomes a highly questionable word in Bangladesh. However, what does it mean? And how can Bangladesh make a sustainable economic growth? In general terms, sustainable growth means a rate of growth, which can be maintained without creating other significant economic problems, especially for future generations. If we extend sustainable growth in terms of GDP growth, then indeed Bangladesh is in a way to achieve sustainable growth. Between 2003 from 2017, last 14 years, Bangladesh averaged a GDP growth rate of 6.3%. It is unlikely significant to achieve once 6% GDP growth or higher and plunging in the following year. However, it is difficult to constantly hold the average GDP rate of 6% or higher. In contemporary years, despite political turmoil, Bangladesh has done a great job to hold the GDP at 6% more or less an average economic growth, which is much higher than some other countries in South Asia or South East Asia.
Keywords: the economy of bangladesh; sustainable growth; GD P; per capita